Examining Policy Shifts and Transformations in Indigenous Primary Health Care in Alberta, Canada - Goveas, Danika; Montesanti, Stephanie; Chatwood, Susan; Crowshoe, Lynden Lindsay (Health Reform Observer – Observatoire des Réformes de Santé, 2024)
Primary health care (PHC) transformation continues to be identified as a key pathway to achieve health equity for Indigenous peoples. In Alberta, varying degrees of PHC services exist within First Nations, Métis, and urban contexts that are fragmented, under-resourced, and disconnected from each other, perpetuating existing health inequities. A retrospective policy analysis was conducted to a) analyze federal, provincial, and local policies to advance Indigenous PHC in Alberta; and b) examine the engagement of Indigenous peoples in PHC policy and decision-making. The review found that prior to and into the early 1960s, the federal government controlled Indigenous peoples’ rights to health. By the end of the decade, the federal government shifted their responsibilities to Indigenous peoples in an attempt to reduce their role in health care delivery. In the late 1970s, the federal government reaffirmed their responsibilities in providing PHC to Indigenous peoples by establishing Indigenous-specific policies. This led to the creation of many co-designed reforms and initiatives provincially to increase Indigenous participation in policy throughout the 2000s. Despite these advancements, more work is needed to ensure that health priorities important to Indigenous peoples are appropriately addressed. Future Indigenous PHC-focused policy reforms can enhance Indigenous health experiences by clarifying the roles of federal, provincial, and Indigenous governments in the coordination of PHC; by ensuring Indigenous representation at all relevant decision-making tables; and by actively working to decolonize the health care institution and promote health equity. La transformation des soins de santé primaires (SSP) continue d'être identifiée comme une voie clé pour atteindre l'équité en matière de santé pour les peuples autochtones. En Alberta, il existe divers degrés de SSP au sein des premières nations, des métis et des contextes urbains qui sont fragmentés, manquent de ressources et sont déconnectés les uns des autres, ce ...